Comparative evaluation of the efficacy of a herbal mouthwash and chlorhexidine mouthwash on select periodontal pathogens: An in vitro and ex vivo study - Multazim Muradkhan Pathan (Journal of Indian Society of Periodontology, 2017)
Background: Several herbal mouthwash and herbal extracts have been tested in vitro and in vivo in search of a suitable adjunct to mechanical therapy for long-term use. In this study, we aimed to look at the antimicrobial effect of the herbal mouthwash and chlorhexidine (CHX) mouthwash on select organisms in in vitro test and an ex vivo model. Materials and Methods: The antimicrobial effects were determined against standard strains of bacteria that are involved in different stages of periodontal diseases. The in vitro tests included determination of minimum inhibitory concentration (MIC) using broth dilution and agar diffusion. In the ex vivo part of the study supragingival dental plaque were obtained from 20 periodontally healthy adult volunteers. Descriptive analysis was done for the entire quantitative and qualitative variable recorded. Results: The MIC by broth dilution method found no statistically significant difference between the mouthwashes. The agar dilution method showed CHX was more effective as compared to the herbal mouthwash against standard strains of Streptococcus mutans, Streptococcus sanguinis, and Aggregatibacter actinomycetemcomitans. However, no difference was observed between the mouthwashes for Porphyromonas, Pseudomonas aeruginosa, and Fusobacterium nucleatum. The ex vivo results conclude that none of the selected mouthwashes were statistically significantly different from each other. Conclusion: In the present study, CHX showed higher levels of antimicrobial action than the herbal mouthwash against bacterial species. The results reinforce the earlier findings that the in vitro testing is sensitive to methods and due diligence is needed when extrapolating the data for further use. However, long-term use and in vivo effectiveness against the periopathogens need to be tested in well-planned clinical trials.